The COVID-19 Pandemic Impacts on Youth Mental Health: What We Learn in Four Years - Aqilah Mumtazah; Sawitri, Brihastami; Abdullah Aboutaleb (Faculty of Medicine, Universitas Airlangga, 2026)
Introductions: The COVID-19 pandemic has profoundly impacted many aspects of life, with especially severe effects on social interactions. Quarantine and social distancing measures, while essential for controlling viral spread, imposed unprecedented restrictions on social engagement, intensifying feelings of isolation and stress. This study aims to investigate the short- and long-term effects of the pandemic on youth mental health, a population for whom peer interactions are vital for developmental milestones and overall well-being. Methods: A literature review was conducted, analyzing scientific articles published between 2020 and 2024 that focused on the mental health of youth during and after the COVID-19 pandemic. Results: Evidence indicates a notable increase in depression, anxiety, and other mental health disorders among adolescents and youth during the pandemic. Prolonged periods of home confinement have led to increased feelings of loneliness, which have been linked to elevated risks of depression and suicidal ideation. Furthermore, persistent mental health challenges have been associated with excessive internet use and decreased physical activity during this period—behaviors that continue to adversely affect youth mental health as pandemic restrictions ease. Conclusions: The COVID-19 pandemic has had a significant and lasting impact on youth mental health, largely due to the critical role of social interactions and peer relationships in this age group. Social isolation remains a key factor contributing to ongoing mental health issues even after the pandemic. Given the long-term implications, increased attention and intervention efforts are urgently needed to support youth mental health, especially as this area remains under-researched.